Gut appreciation: possibilities for aesthetic disgust (Lebenswelt. Aesthetics and philosophy of experience., 2013)
Although the arousal of disgust is now widely acknowledged to be an appropriate response to certain works of art, controversy remains regarding whether to consider this emotion an actual zone of appreciative enjoyment. This paper presents several solutions to the so-called paradox of aversion and argues for a brand of aesthetic disgust that produces an experience that can be savored despite its difficult and unpleasant qualities.